2021
DOI: 10.1111/iwj.13687
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of ozone therapy for treating chronically refractory wounds and ulcers

Abstract: This study aims at evaluating the efficacy and safety of ozone therapy for chronic wounds. The Cochrane Library, PubMed, Ovid Embase, Web of Science, and Chinese Biomedical Literature Database were searched. Randomised controlled trials (RCTs) about participants with chronic wounds were included. Risk of bias assessment was performed by the Cochrane risk-of-bias tool. A randomised-effects model was applied to pool results according to the types of wounds or ulcers. Among 12 included studies, ozone was implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 40 publications
(185 reference statements)
0
31
0
4
Order By: Relevance
“…In the international literature, there are many such references to the utilisation of ozonated liquids in clinical practice, 5 implying that these agents are widely used and accepted treatment modalities. A recent systematic review by Wen and colleagues 6 demonstrated that ozone therapy markedly accelerated the improvement of chronic wounds and reduced the amputation rate. Other studies that include liquid forms of O 3 are often of small sample size and lack validation with large randomised controlled trials (RCTs); however, they have shown promising results in the management of venous stasis ulcers, 7 burns, 8 atopic dermatitis, 9 , 10 tinea pedis, 11 , 12 , 13 hand sanitation, 14 diabetic foot ulcers, 15 and other dermatologic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the international literature, there are many such references to the utilisation of ozonated liquids in clinical practice, 5 implying that these agents are widely used and accepted treatment modalities. A recent systematic review by Wen and colleagues 6 demonstrated that ozone therapy markedly accelerated the improvement of chronic wounds and reduced the amputation rate. Other studies that include liquid forms of O 3 are often of small sample size and lack validation with large randomised controlled trials (RCTs); however, they have shown promising results in the management of venous stasis ulcers, 7 burns, 8 atopic dermatitis, 9 , 10 tinea pedis, 11 , 12 , 13 hand sanitation, 14 diabetic foot ulcers, 15 and other dermatologic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these properties, ozone can successfully be used in the treatment of difficult chronic wounds, including infected wounds. [9][10][11]…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of these compounds leads to changes in the permeability of cell membranes and to the secondary oxidation of proteins that are part of the enzymatic system in the cytoplasm, resulting in bactericidal properties. Because of these properties, ozone can successfully be used in the treatment of difficult chronic wounds, including infected wounds 9–11 …”
Section: Introductionmentioning
confidence: 99%
“…Questa tipologia di prodotto presenta ormai una importante letteratura a sostegno. Wen et al, in una recente review della letteratura, 10 riportano l'utilizzo di ozonidi topici nel trattamento di ulcere post attiniche, venose, ulcere digitali in sclerodermia, ulcere arteriose e piede diabetico; a fronte dell'assenza di evidenza nelle lesioni attiniche, in tutte le altre tipologie viene riportata una accelerazione della riparazione ma, i dati, non sarebbero significativi; l'autore sottolinea però un basso livello degli studi. Lim et al, in un'altra review, 11 segnalano un effetto positivo sul wound healing legato all'attività battericida, antifungina ed antivirale degli oli ozonizzati.…”
unclassified